Katajan- ja mustikanversojen kestävä keruu luonnontuotealan raaka-aineeksi - Stark, Sari; Niva, Aarno; Martz, Françoise; Vuorela, Eija (MTT, 2010)
Lapland Mustikanversojen keruu on keskitetty tiheäpuustoisiin kuusikoihin, jotka eivät ole hyviä mustikan marja-alueita. Mustikanversojen koneellinen keruu poistaa noin 20 % maanyläpuolisesta biomassasta. Versokasvuston biomassa uusiutuu leikkaamattomien mustikkakasvustojen tasolle jo seuraavan kasvukauden aikana. Marjasato putoaa keruun jälkeen kahdeksi vuodeksi, mutta palaa leikkaamattomien kasvustojen tasolle kolmantena keruunjälkeisenä vuonna. Kataja toipuu versojen keruusta pääsääntöisesti hyvin. Toipumisnopeuden arviointi perustuu katajan keruualueilla suoritettuihin vuosittaisiin seurantoihin. Keruun vaikutusten havainnoimiseksi käytettiin verrokkeina keräämättömiä katajikoita. Tutkimusten pohjaksi piti katajalle kehittää ensin sopiva inventointimenetelmä ja toipumisen mittaristo. Katajan toipumista selvitettiin myös kontrolloiduilla maastokokeilla. Kun kataja menettää versojaan, se usein lisää seuraavan vuoden kasvuaan, mikä nopeuttaa toipumista. Karuilla kasvipaikoilla toipuminen on hidasta etenkin silloin, jos keruuta seuraavana kasvukautena olosuhteet kasvuun ovat huonot. Biologisesti aktiivisten fenolien pitoisuus on usein korkeampi kerätyissä kuin keräämättömissä katajikoissa, mutta keruulla ei ole vaikutuksia terpeenien eli eteeristen öljyjen pitoisuuksiin. Keruusuosituksilla varmistetaan katajan riittävän neulasbiomassan säilyminen ja turvataan toipuminen epäedullisissakin oloissa.

Since late 1990 s, shoots of naturally growing bilberry (Vaccinium myrtillus) and juniper (Juniperus communis) have been used as raw material for cosmetic and health-promoting products. During the 2000 s the consumption of these raw materials have reached an industrial scale. As the shoot gathering is increasing, it is necessary to determine the recovery of bilberry and juniper after shoot collection. During 2005 2009, a co-operative research project between Finnish Forest Research Institute, Agrifood and Lapland 4H organization was conducted in order to determine the recovery rates of bilberry and juniper by monitoring the sites used for gathering and by controlled field experiments. The aim of the study was to determine whether shoot gathering has any harmful effects on bilberry and juniper, and at which rate the plants compensate for the lost biomass. In the case of bilberry, influences on berry yield were also determined. The shoot gathering is commonly practised in densely forested spruce forests, which generally do not have high berry yields and therefore do not have central role in berry collection. Shoot gathering by machine removes approximately 20 % of the aboveground bilberry biomass. The aboveground biomass renews itself to the uncut levels within one growing season. The berry yield is reduced for two years after shoot gathering and raises back to normal on the third year after the shoot gathering. Juniper most commonly recovers well from shoot gathering. The recovery rate was based on yearly monitoring of the gathering sites. Junipers subjected to shoot gathering were compared to controls with no shoot collection. In the beginning of the project, the investigation required developing suitable methods for inventory and indices for recovery. The responses of juniper to shoot collection were investigated also with controlled experiments. When juniper loses biomass, it often increases growth the next year and by this way, increases the recovery rate. In nutrient-poor and dry conditions, however, the recovery is slow if conditions are environmentally harsh in the following growing season. The concentrations of biologically active compounds, phenolics, are commonly higher in collected than uncollected junipers, but shoot collection does not influence the concentrations of terpenes. The recommendations for shoot collection will ensure the recovery of juniper even in unfavourable environmental conditions.
Keywords: Ka; Ma; Lappi; Mustikka; kataja; luonnontuoteala; marjanpoiminta; kompensaatiokasvu; bilberry; common juniper; natural product industry; berry picking; compensatory growth; Lapland